2005
DOI: 10.1118/1.1852794
|View full text |Cite
|
Sign up to set email alerts
|

Mass density images from the diffraction enhanced imaging technique

Abstract: Conventional x-ray radiography measures the projected x-ray attenuation of an object. It requires attenuation differences to obtain contrast of embedded features. In general, the best absorption contrast is obtained at x-ray energies where the absorption is high, meaning a high absorbed dose. Diffraction-enhanced imaging (DEI) derives contrast from absorption, refraction, and extinction. The refraction angle image of DEI visualizes the spatial gradient of the projected electron density of the object. The proje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
4

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 6 publications
0
13
0
4
Order By: Relevance
“…This is accomplished through two major factors based on the inherent properties of x-rays First, additional contrast is gained by preventing the majority of x-ray scatter from reaching the detector, a source of image degradation in conventional radiography. This is achieved by virtue of the angular sensitivity of the analyzer crystal, the distinguishing feature of ABI8,21,22,23. Secondly, the analyzer crystal allows detection of refracted x-rays and, thus, high sensitivity for delineating the boundaries between tissues having different refractive indices.…”
Section: Discussionmentioning
confidence: 99%
“…This is accomplished through two major factors based on the inherent properties of x-rays First, additional contrast is gained by preventing the majority of x-ray scatter from reaching the detector, a source of image degradation in conventional radiography. This is achieved by virtue of the angular sensitivity of the analyzer crystal, the distinguishing feature of ABI8,21,22,23. Secondly, the analyzer crystal allows detection of refracted x-rays and, thus, high sensitivity for delineating the boundaries between tissues having different refractive indices.…”
Section: Discussionmentioning
confidence: 99%
“…The refractive index decrement of a material, in fact, can be expressed as ¼ ðr 0 2 =2Þ e ' ðr 0 2 =4uÞ ¼ KðÞ, where r 0 is the classical electron radius and u is the unified atomic mass unit [21]. It can be shown that Á y ðÞ¼@ð R dzðÞÞ=@y¼KðÞ@ð R dzÞ=@y [22]; therefore, for a given angular resolution, the corresponding sensitivity to the object mass density variation is equal to ð@ð R dzÞ=@yÞ ¼ ðÁ y Þ=K. For instance, for an object of constant thickness of 1 cm and at an energy of 12 keV, a 13 nrad angular resolution leads to a detectable density gradient of about 9  10 À4 g=cm 3 mm À1 (e.g., a change of less than a thousandth of the density of water over a mm).…”
mentioning
confidence: 99%
“…It is possible by immersing the lenses in a medium of nearly the same density of the lens tissue, de-ionized water has been used for this purpose. 22 A clean uniform low-contrast image is shown in Fig. 3͑c͒ corresponding to the exposure of the healthy lens immersed in water.…”
Section: Resultsmentioning
confidence: 99%